2018
DOI: 10.3390/app8122566
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Monitoring of Parkinson’s Disease Dysgraphia Based on Fractional-Order Derivatives of Online Handwriting

Abstract: Parkinson’s disease dysgraphia affects the majority of Parkinson’s disease (PD) patients and is the result of handwriting abnormalities mainly caused by motor dysfunctions. Several effective approaches to quantitative PD dysgraphia analysis, such as online handwriting processing, have been utilized. In this study, we aim to deeply explore the impact of advanced online handwriting parameterization based on fractional-order derivatives (FD) on the PD dysgraphia diagnosis and its monitoring. For this purpose, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 47 publications
6
23
0
4
Order By: Relevance
“…The evidence presented in Table 8 and Figure 6 supports the notion that FrOr models may be useful in clinical use. The increase in diagnostic accuracy obtained in the present study ( Figure 6) is in close agreement with improvements observed in the differentiation between malignant and benign breast lesions detected on X-ray screening mammography [51], cancer detection [52], screening for hemodialysis patients [53], differentiation of low-and high-grade pediatric brain tumors [54], and Parkinson's Disease severity assessment [55].…”
Section: Discussionsupporting
confidence: 89%
“…The evidence presented in Table 8 and Figure 6 supports the notion that FrOr models may be useful in clinical use. The increase in diagnostic accuracy obtained in the present study ( Figure 6) is in close agreement with improvements observed in the differentiation between malignant and benign breast lesions detected on X-ray screening mammography [51], cancer detection [52], screening for hemodialysis patients [53], differentiation of low-and high-grade pediatric brain tumors [54], and Parkinson's Disease severity assessment [55].…”
Section: Discussionsupporting
confidence: 89%
“…Mucha et al proposed a new methodology for the kinematic feature analysis of PD handwriting based on fractional derivatives of arbitrary order. Promising results using this techniques have been reported in Reference [95].…”
Section: Disease Diagnosismentioning
confidence: 96%
“…We computed the continuous wavelet transform with a Gaussian wavelet. The feature set is formed with the energy content in 8 frequency bands from the scalogram, three spectral centroids, the energy in the in the 1st, 2nd, and 3rd quartiles of the spectrum, the energy content in the locomotor band (0.5-3 Hz), the energy content in the freeze band (3)(4)(5)(6)(7)(8), and the freeze index, which is the ratio between the energy in the locomotor and freeze bands [15,16].…”
Section: Gait Featuresmentioning
confidence: 99%
“…The authors reported moderate Spearman's correlations (ρ=0.42). Handwriting was considered in [6], to predict the H&Y score of 33 PD patients using kinematic features and a regression based on gradient-boosting trees. The H&Y score was predicted with an equal error rate of 12.5%.…”
Section: Introductionmentioning
confidence: 99%